Solvent-free microwave-assisted synthesis of novel pyrazolo [4′, 3′: 5, 6] pyrido [2, 3-d] pyrimidines with potential antifungal activity - Acosta, Paola (2016)
Novel fused pyrazolo[4',3':5,6]pyrido[2,3-d]pyrimidines 5 were prepared by a solvent-free microwave assisted reaction of heterocyclic o-aminonitriles 3 and cyanopyridines 4 in the presence of tBuOK as catalyst. This protocol provides a versatile procedure for the synthesis of the title compounds with the advantages of easy work-up, mild reaction conditions and good yields. All compounds were also tested for antifungal properties against two clinically important fungi; Candida albicans and Cryptococcus neoformans. Several compounds showed moderate activity against both fungi, being 5a the most active compound. Analysis of the antifungal behavior of properly grouped compounds allowed to determine that the position of the N in the pyrimidyl moiety per se does not play a role in the activity. In turn, the type of 4-R substituent appears to influence the activity. In addition to the above considerations, the lipophilicity of compounds measured as log. P showed to be not related to the activity and regarding the dipole moment (D), no net correlation was observed, although it is the most active compounds (% inhibition >50%) that have a D ≥ 7.5, mainly against C. albicans.